Baltic Sea Spray Emissions: In Situ Eddy Covariance Fluxes vs. Simulated Tank Sea Spray - Ernst Douglas Nilsson; Kim A. H. Hultin; Eva Monica Mårtensson; Piotr Markuszewski; Kai Rosman; Radovan Krejci (Atmosphere, 2021)
We present the first ever evaluation of sea spray aerosol eddy covariance (EC) fluxes at near coastal conditions and with limited fetch, and the first over water with brackish water (on average 7 ppt). The measurements were made on the island of Garpen in the Baltic Sea (56°23′ N, 16°06′ E) in September 2005. We found that wind speed is a major factor that is driving an exponential increase in sea spray sea salt emissions, comparable to previous studies over waters with higher salinity. We were able to show that the inclusion of a thermodenuder in the EC system allowed for the parallel measurements of the dry unheated aerosol flux (representing both organic and sea salt sea spray emissions) and the heated (300 °C) non-volatile sea salt emissions. This study’s experimental approach also included measurements of the artificial sea spray formed in a tank in locally sampled water at the same location as the EC fluxes. We attempted to use the EC aerosol flux measurements to scale the tank measurements to aerosol emissions in order to derive a complete size distribution for the sea spray emission fluxes below the size range (0.3–2 µm dry diameter) of the optical particle counters (OPCs) in the EC system, covering in total 0.01 µm to 2 µm diameter. In the wind directions with long fetches (corresponding to conditions similar to open sea), we were able to distinguish between the aerosol emission fluxes of dry aerosol and heated non-volatile (sea salt only) in the smallest size bins of the OPC, and could therefore indirectly estimate the organic sea spray fraction. In agreement with several previous ambient and tank experiments deriving the size resolved chemical mass concentration of sea salt and water-insoluble organic sea spray, our EC fluxes showed that sea sprays were dominated by sea salt at sizes ≥1 µm diameter, and by organics at the smallest OPC sizes. Since we used direct measures of the sea spray emission fluxes, we confirmed previous suggestions that this size distribution of sea salt and organics is a signature of sea spray aerosols. We were able to show that two sea salt source parameterizations (Mårtensson et al. (2003) and Salter et al. (2015)) agreed fairly well with our observed heated EC aerosol emission fluxes, as long as their predicted emissions were modified for the actual salinity by shifting the particle diameters proportionally to the cubic rote of the salinity. If, in addition, we added organics to the parameterized sea spray following the mono-layer model by Ellison et al. (1999), the combined sea spray parameterizations for sea salt and organics fell reasonably close to the observed fluxes for diameters > 0.15 µm, while one of them overpredicted the sea spray emissions below this size. The organic mono-layer model by Ellison et al. appeared to be able to explain most of the differences we observed between the aerosol emission fluxes with and without the thermodenuder.